2019
DOI: 10.1002/ejp.1363
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐movement behaviours when viewing real‐world pain‐related images

Abstract: Background Pain‐related cues are evolutionarily primed to capture attention, although evidence of attentional biases towards pain‐related information is mixed in healthy individuals. The present study explores whether healthy individuals show significantly different eye‐movement behaviours when viewing real‐world pain‐related scenes compared to neutral scenes. The effect of manipulating via written information the threat value of the pain‐related scenes on eye‐movement behaviours was also assessed. Methods Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 60 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…One study found healthy people with higher fear of pain fixated more quickly on sensory pain words than less pain-fearful cohorts during a dot-probe task (d = 0.21) (Yang et al, 2012). However, six studies comprising chronic pain or healthy samples did not find an association between fear of pain and this particular index (Jackson et al, 2018b(Jackson et al, , 2018aSchoth, Wu, et al, 2019;Sharpe et al, 2017;Yang et al, 2013). In relation to moderating effects of pain catastrophising, one study found that low catastrophising healthy participants had shorter first fixation latencies for pained faces than neutral faces during free-viewing, with initial fixation latencies becoming increasing faster with increasing levels of pain expression in images (Vervoort et al, 2013).…”
Section: First Fixation Latencymentioning
confidence: 99%
See 3 more Smart Citations
“…One study found healthy people with higher fear of pain fixated more quickly on sensory pain words than less pain-fearful cohorts during a dot-probe task (d = 0.21) (Yang et al, 2012). However, six studies comprising chronic pain or healthy samples did not find an association between fear of pain and this particular index (Jackson et al, 2018b(Jackson et al, , 2018aSchoth, Wu, et al, 2019;Sharpe et al, 2017;Yang et al, 2013). In relation to moderating effects of pain catastrophising, one study found that low catastrophising healthy participants had shorter first fixation latencies for pained faces than neutral faces during free-viewing, with initial fixation latencies becoming increasing faster with increasing levels of pain expression in images (Vervoort et al, 2013).…”
Section: First Fixation Latencymentioning
confidence: 99%
“…Dot-probe tasks used in eye-tracking studies have been similar to those used in the reaction time literature. In free-viewing tasks, participants were typically asked to freely explore one (Schoth, Wu, et al, 2019) or more (Priebe et al, 2015) visual stimuli simultaneously presented in random locations as if they were watching television. In some studies, participants were informed about locations in which emotional stimuli (i.e., happy or sad face) would appear prior to free-viewing (Giel et al, 2018).…”
Section: Pain and Eye-tracking Measures Of Attentional Biasesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Eye-tracking methodology continuously measures visual-spatial attention and overcomes the shortcomings of a brief snapshot of attentional bias inferred from the visual probe task. 13 Recent eyetracking studies have shown that individuals with chronic pain exhibit greater vigilance to pain-related stimuli and earlier disengagement from pain words. [14][15][16][17] The initial vigilance for pain-related stimuli reflects an adaptive reaction to detect subsequent pain.…”
Section: Introductionmentioning
confidence: 99%